2021
DOI: 10.1002/tqem.21822
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of Ciliwung river and identification of suitable locations to build artificial dams for flood mitigation

Abstract: Flood caused by overflowing water from river has become a major issue in Southeast Asia, as it has caused economic losses and deaths. Therefore, the present work aims to propose an alternative approach for morphometric analysis of the Ciliwung River Upper Stream (CRU) without the geographic information system technique use for flood prevention strategy application. For the river network simulation, an agent‐based model having several rules in terms of agent, landscaping, and action was adopted. In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Accordingly, about seven stream orders for an area of 1500 km 2 Akaki watershed and the total stream length ranges 2204 kms (Table 2 below.) Therefore, having these catchment data, we can compute equations for different characteristics of the watershed using equations [1][2][3][4][5][6].…”
Section: Drainage Densitymentioning
confidence: 99%
“…Accordingly, about seven stream orders for an area of 1500 km 2 Akaki watershed and the total stream length ranges 2204 kms (Table 2 below.) Therefore, having these catchment data, we can compute equations for different characteristics of the watershed using equations [1][2][3][4][5][6].…”
Section: Drainage Densitymentioning
confidence: 99%
“…Alatas et al. (2022) proposed a new concept of morphometric analysis of Ciliwung river by using agent‐based modeling for water resource management. The study successfully modeled complex characteristics of the river and identified locations to build artificial dams which could be implemented for water resource and flood prevention management.…”
Section: Waste Managementmentioning
confidence: 99%